Design of a printed MIMO/diversity monopole antenna for future generation handheld devices. Issue 3 (27th August 2013) - See, C. H.; Abd‐Alhameed, R. A.; McEwan, N. J.; Jones, S. M. R.; Asif, R.; Excell, P. S.
ABSTRACT This article presents a printed crescent‐shaped monopole MIMO diversity antenna for wireless communications. The port‐to‐port isolation is increased by introducing an I‐shaped conductor symmetrically between the two antenna elements and shaping the ground plane. Both the computed and experimental results confirm that the antenna possesses a wide impedance bandwidth of 54.5% across 1.6–2.8 GHz, with a reflection coefficient and mutual coupling better than −10 and −14 dB, respectively. By further validating the simulated and the measured radiation and MIMO characteristics including far‐field, gain, envelope correlation and channel capacity loss, the results show that the antenna can offer effective MIMO/diversity operation to alleviate multipath environments. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:348–359, 2014.